Online Information Sharing on COVID-19 Causes and Preventive Actions among IIUM students - Arrifin, Nur Izzati (Malaysian Association of Educators (MACE), 2021)
COVID-19 has claimed the lives of more than 600 thousand people within half a year. As the pandemic worsens, the number of fake news online also increases. The main objective of this study is to examine online information sharing regarding COVID-19 causes and preventive actions among university students. Specifically, this study examined the perception, attitude, behavior, and online information sharing on COVID-19 causes and preventive actions among International Islamic University Malaysia (IIUM) students. The quantitative research design was employed in this study. The survey method was used with an online questionnaire as the research instrument for data collection. A total of 203 respondents were selected to participate in this study through the network sampling procedure. The study is guided by the social exchange theory. It was found that IIUM students had a positive level of perception, attitude, and behavior towards COVID-19 causes and preventive actions. They also had a high level of online information sharing on COVID-19 causes and preventive actions. The majority of the students shared information about COVID-19 causes and preventive actions with peers through social media. Due to the high level of online information sharing, almost all of IIUM students preferred not to visit people infected with COVID-19 regardless of whether those people are their friends or relatives. Further, IIUM students tended to stay indoors to avoid COVID-19. The findings of the study are expected to have implications on online information sharing and virus outbreak